PELAYANAN RESEPSIONIS DI ARDAN HOTEL BANDUNG - RIZKY SEPTIANDY WIGUNA; SRI MARINI (POLITEKNIK PIKSI GANESHA, 2018)
This study aimed to find out the reception service at Ardan Hotel Bandung.The method used is a quantitative method. The data collection techniques carried out are by distributing questionnaires, observations. While the data analysis technique uses a Likert scale. Based on the results of the study, it can be seen that services based on procedural dimension and conviviality dimension performed by receptionists at Ardan Hotel Bandung are still in the less category. Problems arised in this research: 1) 1. How is the implementation of the procedural dimension conducted at Ardan Hotel Bandung ?; and 2) How is the Conviviality dimension carried out at Ardan Hotel Bandung.